Studies on Drift Gillnet Fishing at Agatti Island (Lakshadweep) - P., Pravin; Thomas, Saly N.; Mathai, George P.; B., Meenakumari; P., Remesan M. (Fishery Technology, 2025)
The results of experimental and pre-commercial fishing operations conducted at Agatti Island during 2003-2006 with large mesh high density polyethylene (HDPE) and polyamide (PA) drift gill nets are presented in the paper. Gill nets can be used effectively in the islands as a diversified fishing method to harvest the vast untapped resources like Thunnus albacares (yellowfin tuna), Thunnus obesus (bigeye tuna), Istiophorus platypterus (sailfish), Makaira spp (marlin) and other large pelagics. Results indicated that large mesh drift gillnets were effective in harvesting large pelagic fishes which are not being exploited by the existing pole and line fishing. This can be taken up successfully in a commercial scale in the Lakshadweep islands.